Dryland No-Till Corn in Western Kansas (W-C-F Rotation) - Sartwelle III, James D.; O'Brien, Daniel M.; Thompson, Curtis R. (My University, 1997)
This publication provides estimated cost and returns for forward farm planning for dryland no-till corn in western Kansas.
MF2150_1997_10
Keywords: MF2150; Crops; Economics; MF